2015
DOI: 10.1007/s13365-015-0370-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic network connectivity abnormalities in HIV-infected individuals over age 60

Abstract: Individuals infected with HIV are living longer due to effective treatment with combination antiretroviral therapy (cART). Despite these advances, HIV-associated neurocognitive disorders (HAND) remain prevalent. In this study, we analyzed resting state functional connectivity (rs-fc) data from HIV-infected and matched HIV-uninfected adults aged 60 years and older to determine associations between HIV status, neuropsychological performance, and clinical variables. HIV-infected participants with detectable plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Structural changes in brain can persist and often worsen over time and volume reductions in multiple brain regions including grey matter, thalamus, caudate, putamen, and hippocampus have been reported 9 , 10 , 12 , 14 , 15 , 44 , 47 , 50 53 . Likewise, functional deficits in network connectivity have been reported in older HIV patients 54 , that are only partially resolved following the initiation of cART 55 . The mechanisms for residual neurological damage in cART treated patients is not entirely clear, but it has been repeatedly proposed to involve the long-term effects of non-structural proteins in brain that continue to be expressed despite cART.…”
Section: Discussionmentioning
confidence: 99%
“…Structural changes in brain can persist and often worsen over time and volume reductions in multiple brain regions including grey matter, thalamus, caudate, putamen, and hippocampus have been reported 9 , 10 , 12 , 14 , 15 , 44 , 47 , 50 53 . Likewise, functional deficits in network connectivity have been reported in older HIV patients 54 , that are only partially resolved following the initiation of cART 55 . The mechanisms for residual neurological damage in cART treated patients is not entirely clear, but it has been repeatedly proposed to involve the long-term effects of non-structural proteins in brain that continue to be expressed despite cART.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in those studies with patients with HAND, 2 of 3 found a relationship to attenuation of the salience network. 10,12 Ipser et al 11 noted a relationship only with the central executive control network, but the study included patients with substance misuse and only 4 patients had HAND. Of potential additional importance is the finding by Guha et al 12 of a reduction in the salience network with an elevated plasma viral load.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Ipser et al 11 noted a relationship only with the central executive control network, but the study included patients with substance misuse and only 4 patients had HAND. Of potential additional importance is the finding by Guha et al 12 of a reduction in the salience network with an elevated plasma viral load. This may be relevant to our findings: it suggests that active HAND, at least in our study, is associated with viral replication in the brain at a level not reflected in the blood or the CSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations